The potential contribution of the natural products from Brazilian biodiversity to bioeconomy - Valli, Marilia [UNESP]; Russo, Helena M. [UNESP]; Bolzani, Vanderlan S. [UNESP] (Acad Brasileira De Ciencias, 2018)
The development of our society has been based on the use of biodiversity, especially for medicines and nutrition. Brazil is the nation with the largest biodiversity in the world accounting for more than 15% of all living species. The devastation of biodiversity in Brazil is critical and may not only cause the loss of species and genes that encode enzymes involved in the complex metabolism of organisms, but also the loss of a rich chemical diversity, which is a potential source for bioeconomy based on natural products and new synthetic derivatives. Bioeconomy focus on the use of bio-based products, instead of fossil-based ones and could address some of the important challenges faced by society. Considering the chemical and biological diversity of Brazil, this review highlights the Brazilian natural products that were successfully used to develop new products and the value of secondary metabolites from Brazilian biodiversity with potential application for new products and technologies. Additionally, we would like to address the importance of new technologies and scientific programs to support preservation policies, bioeconomy and strategies for the sustainable use of biodiversity.
Keywords: Brazilian biodiversity; natural products; medicinal chemistry; database